PENGARUH KINERJA LINGKUNGAN DAN KINERJA KEUANGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR DI BEI - yunus tulak tandirerung; Eko Adi Widyanto; Riski Masitah Rahmah (Jurnal Eksis, 2019)
This study aims to examine the effect of environmental performance and financial performance in corporate social responsibility in manufacturing companies. The company's environmental performance in this study was measured through PROPER (Program Rating of Company Performance in Environmental Management). Financial performance used includes profitability, leverage, and likuiditas. The dependent variable in this study is of corporate social responsibility. The results of this study indicate that  (1) environmental performance has a positive and significant effect on corporate social responsibility, (2) profitability has a negative and not significant effect on corporate social responsibility, (3) Leverage has a negative and not significant effect on corporate social responsibility (4) likuiditas has a negative and not significant effect on corporate social responsibility. (5) Environmental performance, profitability, likuiditas, and Leverage has a positive and significant effect on corporate social responsibility Keywords: corporate social responsibility, environmental performance, financial performance